The Problem of Mutual Understanding across Regional Varieties of English - Sargsyan, Mariana (Armenian Folia Anglistika, 2012)
Recently, linguists have been concerned about the fact that the regional varieties of English are gradually drifting apart from each other. There will come a time when English speakers will have to turn to translators for making communication over everyday topics possible. The article aims to illustrate certain peculiarities observed in the word stock of the regional varieties of English in terms of the development of word meaning. The analysis of the factual material reveals that they are largely conditioned by the certain culture belonging of the given nation.